A bibliometric analysis of food security and urbanization: insights and implications - Wei, Yujun; Wei, Xiaokun; Ye, Zhonghua; Fan, Jie (Frontiers in Sustainable Cities, 2025)
This study conducts a comprehensive bibliometric analysis of the intersection between Food Security and Urbanization (FSU), aiming to identify key themes, emerging trends, and research gaps. Using statistical analysis, co-word analysis, and social network analysis, we map the intellectual landscape and global collaboration networks in FSU research. The findings reveal the dominant contributions from the United States and China, with China’s extensive international collaborations highlighting opportunities for future research. A key observation is the disconnect between urbanization and food security studies, underscoring the need for a more integrated approach to research. The study extends Sustainable Development Theory and Urban Metabolism Theory by incorporating socio-economic and environmental dimensions, demonstrating that urbanization’s impact on food security differs across developed and developing countries. The research highlights emerging interdisciplinary themes, such as urban agriculture and socio-economic resilience, aligning with SDG 2 (Zero Hunger) and SDG 11 (Sustainable Cities and Communities). This study lays the foundation for future research on the synergies between urbanization and food security, promoting a more sustainable development trajectory.